Ozone Mitigates the Adverse Effects of Diesel Exhaust Pollutants on Ground-Active Invertebrates in Wheat - Ryalls, James M. W.; Staton, Tom; Mullinger, Neil J.; Bromfield, Lisa M.; Langford, Ben; Pfrang, Christian; Nemitz, Eiko; Blande, James D.; Girling, Robbie D. (Frontiers in Ecology and Evolution, 2022)
There is growing evidence to demonstrate that air pollution is affecting invertebrates both directly (e.g. causing physiological stress responses) and indirectly (e.g. via changes in host plant chemistry and/or by disruption of communication by volatile odours). Many of the studies to-date have focused upon winged insects and disruption of in-flight foraging. Therefore, in this study we investigated how the community composition of predominantly ground-dwelling invertebrates in fields of winter wheat are affected by two of the most ubiquitous lower tropospheric air pollutants, diesel exhaust emissions (including nitrogen oxides – NOx) and ozone (O3), both individually and in combination, over two years. Pitfall traps, located within the rings of a Free-Air Diesel and Ozone Enrichment (FADOE) facility, were used to sample invertebrates. The facility consisted of eight 8 m-diameter rings, which allowed elevation of the pollutants above ambient levels (ca 49-60 ppb NOx and 35-39 ppb O3) but within levels currently defined as safe for the environment by the Environmental Protection Agency. The invertebrates collected were taxonomically identified and characterised by diet specialisation, mobility and functional group. Taxonomic richness and Shannon’s diversity index were calculated. Even under the relatively low levels of air pollution produced, there were adverse impacts on invertebrate community composition, with greater declines in the abundance and taxonomic richness of invertebrates in the diesel exhaust treatment compared with O3 treatment. In the combined treatment, pollutant levels were lower, most likely because NOx and O3 react with one another, and consequently a lesser negative effect was observed on invertebrate abundance and taxonomic richness. Specialist-feeding and winged invertebrate species appeared to be more sensitive to the impacts of the pollutants, responding more negatively to air pollution treatments than generalist feeders and wingless species, respectively. Therefore, these results suggest a more severe pollution-mediated decline in specialist- compared with generalist-feeding invertebrates, and in more mobile (winged) individuals. Understanding how invertebrate communities respond to air pollutants alone and in combination will facilitate predictions of how terrestrial environments respond to changes in anthropogenic emissions, especially as we shift away from fossil fuel dependence and therefore manipulate the interactions between these two common pollutants.